The fullfillment of the principle of truth in civil procedure and the burden of proof and the burden of argumentation - Krok, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The purpose of the paper is to analyze, how rules of the burden of proof and rules of the burden of argumentation justify a thesis, which is found as a true statement by court. Two concepts of the truth discussed in the Polish civil procedure (the objective/material truth and the judicial truth) are compared in connection with the rules of the burden of proof and the burden of argumentation. The rules of burden of proof and the rules of the burden of argumentation are constitutive rules. They state under what conditions a thesis counts as justified. The justification of a decision of applying law based on the rules of the burden of proof or rules of the burden of argumentation is institutional, not substantial.